The life cycle of two paralytic shellfish toxin producing dinoflagellates, Alexandrium minutum and Alexandrium tamiyavanichii (Dinophyceae) in Malaysia / Liow Guat Ru - Liow , Guat Ru (2017)
Hundreds of marine and brackish water dinoflagellates are associated with the natural phenomenon called harmful algal blooms (HABs). HAB is known to cause negative impacts to coastal ecosystems and threaten human lives by contaminating seafood. The dinoflagellates Alexandrium minutum and A. tamiyavanichii are capable of producing the sodium channel-blocking neurotoxins, saxitoxins (STXs). The purpose of this study is to investigate the dynamics and life cycle transitions of these two species in Malaysian waters in order to understand the triggering environmental factors in formation of blooms. Field sampling was undertaken at two paralytic shellfish poisoning (PSP) hotspots, Tumpat, Kelantan and Kuantan Port, Pahang. Clonal cultures of A. tamiyavanichii were established from Kuantan Port, and A. minutum from Tumpat. Microscopic enumeration coupled with quantitative qPCR assay was used to detect the low cell abundance of toxic Alexandrium species in both the motile vegetative cell and dormant resting-cyst phases in Kuantan Port. The results from a 14-months survey showed that cell abundance up to 17 cells m-3 of A. tamiyavanichii was present between April 2015 and May 2016. In order to understand the bloom dynamics in relation to the life cycle transitions, A. minutum were used in cross-mating and cyst germination experiments. The results revealed that the period of encystment-excystment for A. minutum were relatively short (~10 days). This study provides baseline data for future predictive modelling study and early warning of HABs, particularly A. minutum and A. tamiyavanichii.